2020
DOI: 10.5604/01.3001.0014.6579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health staff working the night shift on nutrition, anthropometric measurements, and the risk of cardiovascular disease: A sample from Samsun Province in Turkey

Abstract: Purpose: To determine effect of working in the night shift system on nutritional status, anthropometric measurements, and risk of cardiovascular disease of health staff. Materials and Methods: This cross-sectional study was conducted between August-November 2017 at Samsun Ondokuz Mayıs University among 111 health staff. Data was collected with a questionnaire form including questions about demographic characteristics, nutritional status and anthropometric measurements. SPSS 21.0 statistical package program was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, individuals with ON spend more time and effort on purchasing, planning, and preparing food to consume healthy and pure meals [11]. The obsessive symptoms seen in ON compels individuals to adopt strict diets or to remove essential nutrients from their diets, and therefore, inadequate, and unbalanced nutrition can occur [12][13][14]. In recent years, ON has gained increased attention in scientific research [15] and studies have been conducted to determine whether orthorexic behaviours are observed in patients with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individuals with ON spend more time and effort on purchasing, planning, and preparing food to consume healthy and pure meals [11]. The obsessive symptoms seen in ON compels individuals to adopt strict diets or to remove essential nutrients from their diets, and therefore, inadequate, and unbalanced nutrition can occur [12][13][14]. In recent years, ON has gained increased attention in scientific research [15] and studies have been conducted to determine whether orthorexic behaviours are observed in patients with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Although not yet accepted as a formal medical condition, "orthorexia nervosa" is a growing and important health problem according to many health professionals [5,9]. The obsessive situation seen in orthorexia pushes individuals to adopt strict diets or to remove essential nutrients from their diets, and therefore, inadequate and unbalanced nutrition can be seen in individuals with these characteristics [5,10,11].…”
Section: Introductionmentioning
confidence: 99%